Juridical Analysis of Witness Testimony De Auditu in the Case of Sexual Abuse of Minors - Moh. Eka Valen Arman; Yusrianto Kadir; Roy Marthen Moonti; Muslim A. Kasim (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to juridically analyse the use of testimonial witness testimony de auditu in cases of sexual abuse of minors with a case study of case number 26/Pid. Sus/2024/PN Lbo. In the context of criminal law, testimonial witness testimony de auditu refers to a statement submitted by a witness regarding what he heard from another party, which cannot be used as direct valid evidence, but can provide relevant clues. This research examines the admissibility and influence of such testimony on evidence in cases of child sexual abuse, as well as its relevance in the Indonesian criminal justice system. The method used is Empirical approach by analysing legal practices, as well as related court decisions. The results showed that de auditu testimony has limitations in terms of evidentiary power, its use in cases of child sexual abuse, de auditu witness testimony should be accepted, but must be supplemented with additional evidence such as medical examinations, digital evidence, or witnesses who can confirm the event. Judges should prioritise the principles of caution, objectivity and fairness in evaluating such testimony, to ensure that the decision made is not only fair to the victim but also to the defendant.